Insulin resistance in obese adolescents - Rojas-Gabulli, Maria Isabel (2010)
Introduction: Obesity in children and adolescents is a public health problem that is increasing worldwide, being known its relation with the development of metabolic alterations like diabetes mellitus type 2. Objectives: To determine the presence of insulin resistance in obese and non obese adolescents according to sex, age, pubertal stage and presence of familial metabolic or cardiovascular disorders. Design: Cross-sectional observational and analytical study. Setting: Three Lima urban educational centers. Participants: Adolescents 10 to 17 year-old. Interventions: Sixty nine adolescents between 10 and 17 years old were divided in two groups according to the presence of obesity. Obesity was defined as body mass index >95th percentile, 55,1% were male and 44,9% female. Homeostatic model assessment was employed to determine insulin resistance (HOMA-IR) and beta cell function (HOMA%B) in both groups. Lipid levels were measured by the enzymatic method and a questionnaire was applied to determine familial obesity, diabetes mellitus and cardiovascular disease. Spearman correlation and U Mann-Whitney for media comparison tests were employed. Main outcome measures: Basal insuline, total cholesterol, triglicerids, CLDL cholesterol, HOMA IR and HOMA%B in obese and non obese adolescents. Results: Basal insulin, cholesterol, triglycerides, VLDL cholesterol, HOMA IR and HOMA%B were significantly higher (p<0,05) in the obese group. HOMA –IR showed a weak inverse correlation with Tanner stage in females. Cardiovascular disease and obesity predominated in the obese group families (71,8%). Conclusions: The use of HOMA along with familial disorders identification in obese adolescents is recommended in order to incorporate them in a healthy lifestyle program.